(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This article discusses essential aspects of workwear designed for extreme cold conditions, emphasizing the importance of selecting proper clothing to ensure both comfort and safety. It explains the benefits of a layered clothing system, where each layer—base, mid, and outer—plays a crucial role in thermal regulation and protection against cold weather